Biochemical events associated with rust resistance in sunflower - Mohase, Lintle (University of the Free State, 2003)
English: The biochemical resistance response of sunflower (Helianthus annuus L.) to rust (Puccinia helianthi Schw., pathotype UVPhe 2) was investigated in a comparative study using susceptible (S37-388) and resistant (PhRR3) sunflower cultivars and related to rust development. In addition, the potential of a plant activator, benzothiadiazole (BTH), to induce rust resistance in susceptible sunflower was investigated. Rust infection induced higher enzyme activities of the apoplastic pathogenesis-related (PR) proteins, β-1,3-glucanase, chitinase and peroxidase in the resistant than susceptible plants. The accumulation of β-1,3-glucanase isoenzymes was confirmed by Western blots. According to the labelling data of the immunogold localisation studies, β-1,3-glucanases were concentrated in the mesophyll cell walls during the rust resistance response. As the enzyme activities of the PR proteins were induced, the development of infection structures in the resistant plants was retarded, i.e. the number of vesicles, infection hyphae and haustorium mother cells. An early transient accumulation of H2O2 in the infected resistant plants is proof of the involvement of active oxygen species (AOS) in the resistance response. Active oxygen species’ burst correlated with an early induction (after 3 h of infection) of the activities of AOS-generating enzymes, NADPH oxidase, superoxide dismutase (SOD) and the NADH-dependent peroxidase. The phenolic, salicylic acid (SA), has been implicated in the resistance response as a potential signal molecule. The increase in SA content occurred with a concomitant increase in the activity of phenylalanine ammonia-lyase (PAL), a key enzyme in the synthesis of phenolic compounds. Induction of the activity of lipoxygenase, a key enzyme in lipid biosynthesis, in infected resistant plants, suggests that lipid-derived signals may play a role in the rust resistance response. As rust infection progressed, the number of aborted substomatal vesicles increased in resistant than susceptible plants. The number of infection hyphae, haustorium mother cells and rust colonies, which all favoured disease expression, were lower in the resistant than susceptible plants. Furthermore, in the resistant cultivar, haustorium mother cells were more often associated with host cell necrosis. The hypersensitivity index exceeded one, 96 hours after infection, indicating that the resistant plants were exhibiting the hypersensitive reaction (HR). Since it was found that SA is a possible signal for rust resistance reactions, the effectiveness of BTH, a functional analogue of SA, to induce the resistance response was investigated. This was measured in terms of activities of defence-related enzymes, β-1,3-glucanase and peroxidase. Benzothiadiazole induced an increase in the activities of these enzymes and further reduced disease symptoms by about 30%. In this study some of the biochemical components of the rust resistance response in sunflower have been identified and related to the development of rust infection structures. Furthermore, the potential of BTH as a plant activator in the control of rust diseases in sunflower has been demonstrated. The information gathered in this study contributes to a better understanding of the mechanisms in sunflower involved in rust resistance, which eventually could help to manipulate sunflower for improved resistance.

Afrikaans: Die biochemiese weerstandsrespons van sonneblom (Helianthus annuus L.) teen roes (Puccinia helianthi Schw.) is in ’n vergelykende studie in vatbare (S37-388) en weestandbiedende (PhRR3) kultivars ondersoek en met roesontwikkeling gekorrelleer. Hierbenewens is die potensiaal van ’n plantaktiveerder bensotiadiasool (BTH), om roesweerstand in vatbare sonneblom te induseer, ondersoek. Roesinfeksie het hoër ensiemaktiwiteite van die apoplatiese patogeneseverwante (PR) proteïene, β-1,3-glukanase, chitinase en peroksidase in weerstandbiedende as vatbare plante geïnduseer. Die akkumulering van β-1,3-glukanase-isoensieme is met Westernkladanalise bevestig. Volgens die etiketteringsdata van die immunogoudlokaliseringstudies was β-1,3-glukanases in die mesofilselwande tydens die roesweerstandsrespons gekonsentreer. Die geïnduseerde PR-proteïenensiemaktiwiteite het met vertraging in die ontwikkeling van infeksiestrukture in weerstandbiedende plante gepaard gegaan. Dit het die aantal visikels, infeksiehifes en houstoriummoederselle behels. ’n Vroeë kortstondige H2O2-akkumulering in geïnfekteerde weerstandbiedende plante is bewys van die betrokkenheid van aktiewe suurstofspesies (AOS) by die weerstandsrespons. Die AOS-uitbarsting het met die vroeë induksie (na 3 ure infeksie) van die aktiwiteit van AOS-opwekkingsensieme, NADPH-oksidase, superoksieddismutase (SOD) en die NADH-afhanklike peroksidase gekorreleer. Die fenol, salisielsuur (SA), is as ’n moontlike seinmolekuul by die weerstandsrespons betrek. Die toename in SA-inhoud het met in toename in die aktiwiteit van fenielalanienammoniakliase (PAL), ’n sleutelensiem in die sintese van fenoliese verbindings, gepaard gegaan. Induksie van die aktiwiteit van lipoksigenase, ’n sleutelensiem in lipiedbiosintese, dui daarop dat lipiedverwante seine moontlik ’n rol by die roesweerstandsrespons speel. Soos roesinfeksie vorder, het die aantal geaborteerde substomatale vesikels meer in weerstandbiedende as in vatbare plante geword. Die aantal infeksiehifes, houstoriummoederselle en roeskolonies, wat almal siekte-ontwikkeling bevorder, was minder in weerstandbiedende as vatbare plante. Boonop was die houstoriummoederselle meer dikwels met gasheerselnekrose in die weerstandbiedende kultivar geassosieer. Die hipersensitiwiteitsindeks was 96 uur na infeksie hoër as een in weerstandbiedende plante wat ’n aanduiding van die hipersensitiewe reaksie (HR) in aksie is. Omdat bevind is dat SA ’n moontlike sein vir roesweerstandsreaksie is, is die doeltreffendheid van BTH, ’n funksionele analoog van SA, om die weerstandsrespons te induseer, ondersoek. Dit is ’n terme van die aktiwiteite van die verdedigingsverwante ensieme, β-1,3-glukanase en peroksidase gemeet. Bensotiadiasool het ’n toename in die aktiwiteite van hierdie ensieme geïnduseer en het boonop die siektesimptome met 30% verminder. In hierdie studie is sommige van die biochemiese komponente van die roesweerstandsrespons in sonneblom geïdentifiseer en in verband gebring met die ontwikkeling van roesinfeksiestrukture. Verder is die potensiaal van BTH as plantaktiveerder vir die beheer van sonneblomroessiektes aangetoon. Die inligting ingewin in hierdie studie dra by tot ’n beter begrip van die meganismes in sonneblom betrokke by roesweerstand wat uiteindelik sal help om sonneblom vir beter weerstand te manipuleer.
Keywords: Thesis (Ph.D. (Plant Sciences: Botany))--University of the Free State, 2003; Active oxygen species; Chitinase; Defence reactions/mechanisms; β-1,3-glucanase; Hydrogen peroxide; Lipoxygenase; NADPH oxidase; Pathogenesis related proteins; Peroxidase; Phenylalanine ammonia-lyase; Salicylic acid; Signalling; Sunflower; Sunflower rust; Superoxide dismutase; Rust diseases -- South Africa; Sunflowers -- Diseases and pests -- South Africa; Sunflowers -- Disease and pest resistance -- South Africa